Environmental Sustainability at the Olympic Games: Comparing Rio 2016 and Tokyo 2020 Games - Rowberg, Kathryn; Rincker, Meg (European Journal of Sustainable Development, 2019)
The modern Olympic Games have evolved from events fostering international peace and goodwill to showcases of athleticism and commercialism. More recently sustainability became a pillar of the Game site selection process. This paper focuses on two Olympic Games: Rio 2016 (completed) and Tokyo 2020 (upcoming). The goals of Sustainability Plans and pre-game reports for the two Olympic sites are analyzed using weighted summation method of Multi-attribute Value theory and the framework of environmental, economic and social-cultural sustainability, with emphasis on environmental sustainability. Post-game analysis and legacy stories are reviewed for Rio 2016. Application of legacy stories to future Olympics sites is examined. Last, Rio 2016 and Tokyo 2020, in terms of actual and anticipated success in sustainability initiatives, are compared for the impact these two Games may have on future Olympic Game sites. Keywords: Sustainability, environmental sustainability, Olympic Games, Rio 2016, Tokyo 2020